THE PROBLEM OF ENVIRONMENTAL POLLUTION IN THE MEDITERRANEAN SEA ALONG THE COAST OF TURKEY - ERNUR AKINER MUHAMMED (Journal of Engineering Studies and Research)
Turkish coastline neighbor to the Mediterranean Sea faces serious problems such as eutrophication and diffuse pollution. Among diffuse pollution, the leading actor is intensive agriculture. This research focuses on four developed cities, Antalya, Mersin, Adana, and Hatay, along the Turkish Mediterranean shoreline. The inadequate sewage system and insufficient treatment plants lead to eutrophication in populated cities. In the year 2017, in Turkey's Mediterranean region, Aksu, Manavgat, Göksu, Seyhan, Ceyhan, and Asi rivers were monitored. Concentration values for BOD5, Total Phosphorus, Nitrite Nitrogen, and Nitrate Nitrogen parameters were determined. This study observes the pollution status of the rivers according to the Turkish Water Pollution Control Regulation. One sample T-Test determined the actual pollution potentials of the rivers. Besides, uncontrolled heavy metal and toxic emissions from industry are essential problems.